The hands in the interaction of the individual with himself and the world: a reflection in behalf of the “physical” rehabilitation - Alves de Almeida Fernandes Leite, Telma (O Mundo da Saúde, 2006)
In this article one made efforts to reflect on the essence of “physical” rehabilitation using the hands as an example. The applied methodology was a bibliographical survey, relative to the subject both in the areas of Rehabilitation, Occupational Therapy and the holistic paradigm and on the assumptions of other areas of knowledge, gathering from each area material essential for a deeper reflection in order to reach to a broader conception, one that offers a basis for the praxis of professionals of the rehabilitation area. Thus, the method, in this work of reflection, stops being an instrument and it identifies itself with the movement of consciousness itself. Observing the evolution of health practices one perceives that they had begun with a more integral conception of the human being interacting with the environment. Gradually this conception was overcome by the reductionistic paradigm and today a persistence can be noticed on going back to the holistic conception. It is observed that to qualify or to rehabilitate means going far beyond favoring the ability for the mechanic function, it means creating conditions for the individual to develop abilities, attitudes and values that can reflect conscious action as a continuous and dynamic process of constitution of the identity of the subject historically contextualized. One perceives that besides studyingAnatomy, Biomechanics, Kinesiology and others discipline that refers to the physical, it is critical to understand that human activity goes beyond mechanized movements established for a body that occupies an objective, fixed place in space, but establishes dialectical relations that sprout from its very essence, from the union of the subjectivity that enlivens it.